Bimodal coupling of ripples and slower oscillations during sleep in patients with focal epilepsy. (26th September 2017) - Song, Inkyung; Orosz, Iren; Chervoneva, Inna; Waldman, Zachary J.; Fried, Itzhak; Wu, Chengyuan; Sharan, Ashwini; Salamon, Noriko; Gorniak, Richard; Dewar, Sandra; Bragin, Anatol; Engel, Jerome; et al.
Summary: Objective: Differentiating pathologic and physiologic high‐frequency oscillations (HFOs) is challenging. In patients with focal epilepsy, HFOs occur during the transitional periods between the up and down state of slow waves. The preferred phase angles of this form of phase‐event amplitude coupling are bimodally distributed, and the ripples (80–150 Hz) that occur during the up‐down transition more often occur in the seizure‐onset zone (SOZ). We investigated if bimodal ripple coupling was also evident for faster sleep oscillations, and could identify the SOZ. Methods: Using an automated ripple detector, we identified ripple events in 40–60 min intracranial electroencephalography (iEEG) recordings from 23 patients with medically refractory mesial temporal lobe or neocortical epilepsy. The detector quantified epochs of sleep oscillations and computed instantaneous phase. We utilized a ripple phasor transform, ripple‐triggered averaging, and circular statistics to investigate phase event‐amplitude coupling. Results: We found that at some individual recording sites, ripple event amplitude was coupled with the sleep oscillatory phase and the preferred phase angles exhibited two distinct clusters (p < 0.05). The distribution of the pooled mean preferred phase angle, defined by combining the means from each cluster at each individual recording site, also exhibited two distinct clusters (p < 0.05). Based on the range of preferred phase angles defined by these two clusters, we partitioned each ripple event at each recording site into two groups: depth iEEG peak‐trough and trough‐peak. The mean ripple rates of the two groups in the SOZ and non‐SOZ (NSOZ) were compared. We found that in the frontal (spindle, p = 0.009; theta, p = 0.006, slow, p = 0.004) and parietal lobe (theta, p = 0.007, delta, p = 0.002, slow, p = 0.001) the SOZ incidence rate for the ripples occurring during the trough‐peak transition was significantly increased. Significance: Phase‐event amplitude coupling between ripples and sleep oscillations may be useful to distinguish pathologic and physiologic events in patients with frontal and parietal SOZ.